Genomic Analysis of an Escherichia coli Sequence Type 167 Isolate Harboring a Multidrug-Resistant Conjugative Plasmid, Suggesting the Potential Transmission of the Type Strains from Animals to Humans - Pan S; Liu S; Tai S; Yu J; Yuan E; Duan Y (Infection and Drug Resistance, 2023)
Sijia Pan,1,* Shuangqing Liu,2,* Shuhong Tai,1 Jing Yu,1 Enwu Yuan,1 Yitao Duan1 1Department of Clinical Laboratory, The Third Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 2Department of Clinical Laboratory, The Second Hospital of Tianjin Medical University, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yitao Duan; Enwu Yuan, Department of Clinical Laboratory, The Third Affiliated Hospital of Zhengzhou University, No. 7 Front Kangfu Street, Zhengzhou, Henan, 450052, People’s Republic of China, Email duanyitao@zzu.edu.cn; yuanenwu@126.comPurpose: The E. coli ST167 clone is the globally dominant ST among extraintestinal pathogenic E. coli (ExPEC) and is frequently associated with carbapenem resistance. This study reports genomic characterization of a pandrug-resistant E. coli ST167 isolate (ECO3183) and the possibility of the type strains’ transmission.Materials and Methods: Antibiotic susceptibility testing was performed using disk diffusion and the VITEK 2 automated system. The E. coli ECO3183 genome was sequenced. We used the genome to analyze the phylogenetic relationship, phylogenetic group, sequence type (ST), acquired antibiotic resistance genes (ARGs), IS elements, genomics islands, the replicon type and transferability of the plasmids. The conjugative transfer of plasmids was assessed using filter mating experiments.Results: ECO3183 contained a 4.87-Mb chromosome and two plasmids [pECO3183-1 (167.63 Kb) and pECO3183-2 (46.16 Kb)]. It belonged to phylogenetic group A, clonal complex 10 (CC10), and ST167. ECO3183 is a pandrug-resistant strain nonsusceptible to 24 tested antimicrobials representing 8 different antimicrobial classes. Among 55 E. coli isolates phylogenetically related to ECO3183, 47% (26/55) were from humans, while 35% (19/55) were from animals. Further analysis revealed that among 1140 ST167 isolates (in the EnteroBase database), 4% (47/1140) originated from environments, 17% (192/1140) were isolated from humans, and 78% (890/1140) were obtained from animals. The pECO3183-1 contained two identical repeats of a 9633 bp region (IS6100-sul1-ΔaadA16-dfrA27-arr-3-aac(6′)-Ib-cr-IS26) and a 17.88-kb resistance island (sul2-aph(3″)-Ib-aph(6)-Id-IS26-Δaph(3′)-Ia-IS26-tet(A)-ΔfloR-ΔISVsa3-IS26-Δaac(3)-IId-IS26-mph(A)), and these three regions contained most of ECO3183 carrying ARGs. It was identified as a conjugative plasmid, which confers MDR resistance and has the potential to spread.Conclusion: ECO3183 exhibited pandrug-resistance phenotype that was mediated by pECO3183-1 carrying MDR ARGs and pECO3183-2 carrying blaNDM-5. Source analysis of strains indicated that ST167 E. coli might be transmitted between species from animals to humans, which needs continued monitoring.Keywords: Escherichia coli, ST167, blaNDM-5, phylogenetic analysis, MDR conjugative plasmids